Linear and Nonlinear Magneto-optical Absorption Coefficients and Refractive Index Changes in Wse2 Monolayer - Van Tung, Luong; Quang Bau, Nguyen; Ngoc Bich, Tran; Tuan Vinh, Pham; Vinh Phuc, Huynh (VNU Journal of Science: Mathematics - Physics, 2021)
This work studies the linear, the third-order nonlinear, and the total optical absorption coefficients (OACs) and the refractive index changes (RICs) caused by both intra- and inter-band transitions in the WSe 2 monolayer. The expression for the OACs and RICs in the presence of a magnetic field as well as the Zeeman and electric fields are found by using the compact density matrix approach. The results show that the spin states strongly affect the OACs and RICs, which display the violet-shift behavior with the increase of the magnetic field. The Zeeman fields do not affect the peak positions but slightly reduce peak intensities. The OACs and RICs due to intra-band transition display only one peak in the THz range, while the inter-band spectra show a series of peaks in the near-infrared optical range, making monolayer WSe 2 be a promising candidate for novel optoelectronic applications.